2021
DOI: 10.1001/jamacardio.2021.0475
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Revacept, a Novel Lesion-Directed Competitive Antagonist to Platelet Glycoprotein VI, in Patients Undergoing Elective Percutaneous Coronary Intervention for Stable Ischemic Heart Disease

Abstract: IMPORTANCEThe assessment of new antithrombotic agents with a favorable safety profile is clinically relevant. OBJECTIVE To test the efficacy and safety of revacept, a novel, lesion-directed antithrombotic drug, acting as a competitive antagonist to platelet glycoprotein VI. DESIGN, SETTING, AND PARTICIPANTSA phase 2 randomized clinical trial; patients were enrolled from 9 centers in Germany from November 20, 2017, to February 27, 2020; follow-up ended on March 27, 2020. The study included patients with stable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(59 citation statements)
references
References 39 publications
(66 reference statements)
1
53
0
1
Order By: Relevance
“…Even dual antiplatelet therapy has been applied in clinical trials (115). However, studies have reported that antiplatelet therapy increases the risk of bleeding and is positively associated with duration of therapy (116). Early and short-term dual antiplatelet therapy for minor stroke or high-risk transient ischemic attack (TIA) has been suggested by the clinical guidelines (116).…”
Section: Translational Approaches To Target Thromboinflammation In (N...mentioning
confidence: 99%
“…Even dual antiplatelet therapy has been applied in clinical trials (115). However, studies have reported that antiplatelet therapy increases the risk of bleeding and is positively associated with duration of therapy (116). Early and short-term dual antiplatelet therapy for minor stroke or high-risk transient ischemic attack (TIA) has been suggested by the clinical guidelines (116).…”
Section: Translational Approaches To Target Thromboinflammation In (N...mentioning
confidence: 99%
“…However, the results of the recently reported ISAR-PLASTER phase 2 trial in 334 patients undergoing elective percutaneous revascularization for coronary artery disease were neutral, demonstrating no differences between the two dosing regimens of revacept compared to placebo regarding the composite endpoint of death or high-sensitivity cardiac troponin increase to at least five times the upper limit of normal within 48 h from randomization, despite the significant reduction of collagen-induced platelet aggregation in the high-dose revacept arm. Bleeding events did not differ significantly between the groups [ 206 ]. Another trial of revacept in patients with symptomatic carotid artery disease is currently ongoing [ 207 ], with its results being eagerly awaited.…”
Section: Therapeutic Approachesmentioning
confidence: 99%
“…| 5 LANGER a phase 2 randomized clinical trial with patients undergoing elective percutaneous coronary intervention (PCI) for stable ischemic heart disease. 15 The authors analyzed a short-term endpoint of a composite of death or myocardial injury, whereby Revacept ® had no significant effect. As expected, bleeding was not increased and further studies are required to finally evaluate the value of this approach for CV patients.…”
Section: Co N Fli C T S O F I Nte R E S Tmentioning
confidence: 99%